Variasi Pertumbuhan dan Estimasi Parameter Genetik Semai Nyawai (Ficus variegata Blume) - Haryjanto, Liliek (Fakultas MIPA UNM, 2017)
Abstract. Growth variation and genetic parameter estimation of Ficus variegata Blume seedlings were done at The Centre for Forest Biotechnology and Tree Improvement, Yogyakarta at 8 months of age. Genetic materials from Banyuwangi population which comprised of 15 families and Cilacap-Pangandaran population comprised of 19 families. The trial was designed as a Randomized Completely Block Design (RCBD) with family as treatment, 3 replications and each replication comprises 10 seedlings. The purpose of this study was to observe growth variation and genetic parameter of these populations at seedlings level. Analysis of variance was performed to find out family effect on height and diameter traits. Analysis of variance component was used to estimate coefficient of genetic variation, heritability and genetic correlation. This study showed that family effect on height and diameter variation was very significant at both populations. The estimation of coefficient of genetic variation for height and diameter trait ranged from 10.80% (categorized as intermediate) to 18.04% (categorized as high). Family heritability estimation for height trait ranged from 0.96 to 0.99 and diameter trait ranged from 0.89 to 0.96, both categorized as high. Strong genetic correlation for height and diameter trait ranged from 0.87 to 0.89.Keywords: Nyawai, Ficus variegata, growth, genetic parameter, seedling.